2021
DOI: 10.1002/chem.202005217
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Shape Evolution of Pure‐MOF 1D Microcrystals towards Efficient Waveguide and Laser Applications

Abstract: MOF‐based one‐dimensional materials have received increasing attention in the nanophotonics field, but it is still difficult in the flexible shape evolution of MOF micro/nanocrystals for desired optical functionalities due to the susceptible solvothermal growth process. Herein, we report on the well‐controlled shape evolution of pure‐MOF microcrystals with optical waveguide and lasing performances based on a bottom‐up and top‐down synergistic method. The MOF microcrystals from solvothermal synthesis (bottom‐up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…HOF-FJU-4 and HOF-FJU-5 microwires with conformation-controlled emission properties offer the promising platforms to build wavelength-tunable lasing in HOFs. Here, an individual HOF-FJU-4 microwire is optically pumped by a focused laser beam in a micro-PL system (Figure S13), 50 and bright blue emission spots were obtained from two tips of the microwire (Figure 4A). The obtained PL spectra generated several sharp optical-mode peaks.…”
Section: Resultsmentioning
confidence: 99%
“…HOF-FJU-4 and HOF-FJU-5 microwires with conformation-controlled emission properties offer the promising platforms to build wavelength-tunable lasing in HOFs. Here, an individual HOF-FJU-4 microwire is optically pumped by a focused laser beam in a micro-PL system (Figure S13), 50 and bright blue emission spots were obtained from two tips of the microwire (Figure 4A). The obtained PL spectra generated several sharp optical-mode peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike most existing NLO organic and inorganic crystals, MOFs possess a unique combination of organic-inorganic nature inside a crystal of arbitrary crystal symmetry, with relatively large unit cells and diverse (weak and strong) chemical bonding [7]. Recently, a series of experimental studies have demonstrated the possibility of efficient utilizing MOFs for coherent light emission in the laser regime [8][9][10], coherent and incoherent light conversion [11][12][13][14], white light [15] and quantum light emission [16,17], nonlinear optical absorption [18][19][20][21] and encryption [22][23][24], as well as for optical data transferring [25][26][27][28][29] even at ultrafast regime [30,31]. In most of the above cases, MOFs can be considered as competitive or even superior to commercial NLO crystals, combining it with the simplicity of their synthesis and scalability [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Crystals with nano/microtubes often have important applications, such as storage and release solutions, 10 optical waveguides, [11][12][13][14] micromachines, [15][16][17] and electrochemical energy storage. 18 In particular, fluorescent nano/microtubes together with a colorful infill might result in dynamic multicolor photonic barcodes.…”
Section: Introductionmentioning
confidence: 99%